2012
DOI: 10.1002/jor.22111
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration and recovery of the neuromuscular junction after application of extracorporeal shock wave therapy

Abstract: It is known that free nerve endings are degenerated after application of shock waves. We therefore hypothesized that the application of shock waves to muscle induces dysfunction of neuromuscular transmission at neuromuscular junctions. We investigated changes in neuromuscular transmission in response to shock wave application. Sprague-Dawley rats were used in this study. Two thousand shock waves at an energy flux density of 0.18 mJ/mm 2 were applied to their right calf muscles. Neuromuscular junctions of gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 15 publications
3
60
1
2
Order By: Relevance
“…This increased density of AChRs thickens the postsynaptic membrane, which may change the acoustic impedance between the presynaptic and postsynaptic membranes. In addition, we previously confirmed the degeneration of AChRs after rESW exposure . Therefore, the high density of AChRs at the end plate may explain why the effect of rESW exposure is confined to end plates.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This increased density of AChRs thickens the postsynaptic membrane, which may change the acoustic impedance between the presynaptic and postsynaptic membranes. In addition, we previously confirmed the degeneration of AChRs after rESW exposure . Therefore, the high density of AChRs at the end plate may explain why the effect of rESW exposure is confined to end plates.…”
Section: Discussionsupporting
confidence: 69%
“…Using the results of our previous report (difference in mean amplitude, 10.0 mV; SD, 7.0), we calculated the sample size required to show a significant reduction in CMAP amplitude with a statistically significant P value of 0.05 and power of 0.80. This analysis indicated that more than 9 limbs per group were required, so we measured the CMAP in 10 rats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies explained the mechanism as the effect of the generation of nitric oxides [14], the effect on spinal cord excitability [15], the effect of mechanical vibration [15], the effect on the golgi tendon organ [10], or the passive stiffness of muscles determined by inactive connective tissues [8]. Considering the known fact that the nitric oxides generated by ESWT involve the formation of neuromuscular junctions in the peripheral nervous system and play important roles in neurotransmission, memories, and synaptic plasticity in the central nervous system [16,17] along with a recent report from an interesting study conducted with rats indicating that spasticity was relived because neuromuscular transmission was hindered by ESWT in neuromuscular junctions [18], nitric oxides seem to play core roles in spasticity-relieving mechanisms. Because F-wave and H-reflex related variables showed no differences between before and after treatment in previous studies in which the neurophysiological evaluations were conducted, the effect on spinal cord excitability appears to be small [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Kenmoku et al observed rapid degeneration of acetylcholine receptors after SWT application and pointed out that these consequences were very similar to those of a neuromuscular transmission inhibitor like botulinum toxin. However, unlike botulinum toxin, no obvious weakness in the target muscle [34]. Chronic spasticity itself would further worsen joint resistance through fibrosis of inactive connective tissue due to structural and mechanical changes in the muscle [35].…”
Section: Methodsmentioning
confidence: 99%